2015
DOI: 10.1007/s00270-015-1080-9
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Arterial Chemoembolization with Irinotecan-Loaded Drug-Eluting Beads (DEBIRI) and Capecitabine in Refractory Liver Prevalent Colorectal Metastases: A Phase II Single-Center Study

Abstract: DEBIRI with capecitabine seem to be a safe, technically feasible and well-tolerated treatment in chemotherapy refractory liver prevalent colorectal metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Seven studies graded toxicity according to the National Cancer Institute's Cancer Therapy Evaluation Program Common Toxicity Criteria v2.0 (CTC) or the more modern Common Terminology Criteria for Adverse Events v3.0 (CTCAE). Descriptively, four Y-90 studies, 19,22,23,26 reported on 12-29% of patients experiencing severe to life-threatening adverse events (Grade 3-4), compared to 3-10% of patients in two DEB-TACE studies, 28,29 and 0.4% in one cTACE study. 30 Instances of 30-day mortality and/or procedure-related mortality were rare across all studies, occurring in one, two and three patients in cTACE, DEB-TACE and Y-90 studies, respectively.…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Seven studies graded toxicity according to the National Cancer Institute's Cancer Therapy Evaluation Program Common Toxicity Criteria v2.0 (CTC) or the more modern Common Terminology Criteria for Adverse Events v3.0 (CTCAE). Descriptively, four Y-90 studies, 19,22,23,26 reported on 12-29% of patients experiencing severe to life-threatening adverse events (Grade 3-4), compared to 3-10% of patients in two DEB-TACE studies, 28,29 and 0.4% in one cTACE study. 30 Instances of 30-day mortality and/or procedure-related mortality were rare across all studies, occurring in one, two and three patients in cTACE, DEB-TACE and Y-90 studies, respectively.…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…In recent years, there have been an increasing number of studies into using DEB-TACE to treat liver metastasis of colorectal cancer. It is reported to be safe and feasible to embolize patients with liver metastasis of colorectal cancer with DEB loaded with irinotecan (DEBIRI) [ 7 , 8 ]. A comparative study of the efficacies of embolization (DEBIRI) and intravenous chemotherapy (FOLFIRI regimen) showed that there were longer progression free survival (PFS) and overall survival (OS) in the DEBIRI group than in the FOLFIRI group, and there were less systemic adverse reactions in the DEBIRI group [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…One week after the operation, the ALT and AST of the 2 groups increased, which indicated that both DEB-TACE and c-TACE caused transient injury to the hepatocytes, possibly due to chemotherapeutic drug injury, ectopic embolization, etc. C-TACE has been used for metastatic liver cancer for many years, but the side effect of embolization affects the treatment compliance and efficacy, which is closely related to the skill of the clinician [ 8 ]. DEB-TACE and c-TACE may increase the risk of ectopic embolism and hepatocyte injury in patients with poor hepatic artery supply.…”
Section: Discussionmentioning
confidence: 99%
“…An additional group was LP-irinotecan TACE as a combination treatment with ablation with a curative intent. Typically, TACE with irinotecan is mainly used as a salvage therapy, with no consistent definitions of the number of previous lines of chemotherapy across already published studies [27][28][29][30] . Furthermore, evaluation of treatment intention is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…PES (grade 1) is also the most common adverse events (AE) by far in this interim analysis. While the number of reported grade 1 and grade 2 AEs varied highly, most studies reported none [36,41,42]] or below 10% [10,27,31,43] adverse events of grade 3 and 4. This is in line with what was observed in CIREL with 10% of grade 3 reported adverse events and only 4% of grade 4 in this interim analysis.…”
Section: Discussionmentioning
confidence: 99%